Four cases with ectrodactyly, ectodermal dysplasia, cleft lip/palate syndrome: Clinical evaluation and management and literature review - Gül Trabzon; Ülkü Gül Şiraz; Zeynep Uzan Tatlı; Merve Nur Hepokur; Leyla Akın; Nihal Hatipoğlu; Tamer Güneş (Trends in Pediatrics)
A rare syndrome is ectrodactyly-ectodermal dysplasia-cleft lip/palate (EEC) syndrome, which may present with lobster claw deformity. The main clinical characteristics indicate involvement of ectodermal and mesodermal tissues, including mesoaxial and longitudinal defect of distal extremity, cleft lip and palate, and developmental defects of ectoderm derives. Renal anomalies and hormonal disorders may be seen in EEC patients. This article discusses endocrine problems in 4 EEC patients diagnosed based on clinical characteristics.